The add on effect of Platelet Rich Plasma in management of Dushtavrana: A Case Study - Sindhu Das,; Omprakash Dave,; Manish G, (The Bioscan, 2025)
Wound management principles laid by Acharya Susrutha the father of surgery and the current practice of surgery emphasizes the cosmetic repair of wounds with utmost efficacy. The concept of Shashtirupakrama mentioned by Acharya Susrutha is focused on the Shodhana and Ropana line of management. Platelet-rich plasma (PRP) has been researched and used in various fields of medicine focused on cell-based therapy and tissue engineering. This is a single case study on the management of Dushtavrana focusing on the add-on effect of PRP therapy with classical wound management protocol.